How real is real: attitudes towards realism in selected post-war British fiction - Moghadam, Nahid Shahbazi; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2013)
Despite its apparent precision in meaning, realism as a once-held literary school of thought provokes controversies regarding its basic definition and the works attributed to it. This is particularly the case with the postmodern use of the term, most specifically in relation to fiction, with realism generally asserted as the traditional language of the genre. This paper is an attempt to discuss the implication and tenets of realism, its progress and changes, in selected works of post-war British fiction. Accordingly, Graham Greene’s The Power and the Glory, Mervyn Peake’s Gormenghast, and Ian McEwan’s Atonement are dealt with to trace realism within their respective modes of new realism, fantastic-grotesque and postmodern metafiction. Having survived the early twentieth century allure of modernism, realism has gradually evolved into a new identity capable of emerging in and mingling with new modes prevalent in postmodern fiction. Owing to the spirit of the time immediately following the Second World War and the particularities of different authors, the postmodern realism has gone beyond a mere portrayal of the objective world and is in demand of a refreshed understanding of the new outlooks contemporary realism has the potentiality to offer.